A High-Order Time Domain Discontinuous Galerkin Method with Orthogonal Tetrahedral Basis for Electromagnetic Simulations in 3-D Heterogeneous Conductive Media (Communications in Computational Physics, 2018)
We present a high-order discontinuous Galerkin (DG) method for the timedomain Maxwell's equations in three-dimensional heterogeneous media. New hierarchicalorthonormal basis functions on unstructured tetrahedral meshes are used forspatial discretization while Runge-Kutta methods for time discretization. A uniaxialperfectly matched layer (UPML) is employed to terminate the computational domain.Exponential convergence with respect to the order of the basis functions is observedand large parallel speedup is obtained for a plane-wave scattering model. The rapiddecay of the out-going wave in the UPML is shown in a dipole radiation simulation.Moreover, the low frequency electromagnetic fields excited by a horizontal electricdipole (HED) and a vertical magnetic dipole (VMD) over a layered conductive half-spaceand a high frequency ground penetrating radar (GPR) detection for an undergroundstructure are investigated, showing the high accuracy and broadband simulationcapability of the proposed method.